Competition for in Vitro [(3)H]Gibberellin A(4) Binding in Cucumber by Gibberellins and Their Derivatives - Yalpani, Nasser (1985)
The gibberellin (GA) binding properties of a cytosol fraction from hypocotyls of cucumber (Cucumis sativus L. cv National Pickling) were examined using a DEAE filter paper assay, [(3)H]GA(4), and over 20 GAs, GA derivatives and other growth regulators. The results demonstrate structural specificity of the binding protein for γ-lactonic C-19 GAs with a 3 β-hydroxyl and a C-6 carboxyl group. Additional hydroxylations of the A, C, or D ring of the ent-gibberellane skeleton and methylation of the C-6 carboxyl impede or abolish binding affinity. Bioassay data are generally supported by the in vitro results but significantly GA(9) and GA(36), both considered to be precursors of GA(4) in cucumber, show no affinity for the binding protein. The results are discussed in relation to the active site of the putative GA(4) receptor in cucumber.